2017
DOI: 10.3390/jimaging3030028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Geometric Distortion in Six Clinical Scanners Using a 3D-Printed Grid Phantom

Abstract: A cost-effective regularly structured three-dimensional (3D) printed grid phantom was developed to enable the quantification of machine-related magnetic resonance (MR) distortion. This phantom contains reference features, "point-like" objects, or vertices, which resulted from the intersection of mesh edges in 3D space. 3D distortions maps were computed by comparing the locations of corresponding features in both MR and computer tomography (CT) data sets using normalized cross correlation. Results are reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…of the magnetic field was previously reported by Jafar et al using a 3D-printed grid phantom [14], and such distortion was also observed in our study (Fig 5), causing systematic errors by distorting MRI models anteriorly at the edge of the magnetic field. The effect of distortion on the MRI model was also observed in the subgroup analysis.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…of the magnetic field was previously reported by Jafar et al using a 3D-printed grid phantom [14], and such distortion was also observed in our study (Fig 5), causing systematic errors by distorting MRI models anteriorly at the edge of the magnetic field. The effect of distortion on the MRI model was also observed in the subgroup analysis.…”
Section: Plos Onesupporting
confidence: 90%
“…The maximal difference between the 3D MRI and CT models were 3.491 and 3.160 mm for WE and Dixon methods, respectively, which are within the range of those in the study by Jafar et al [14]. The maximal difference was greatest in the intertrochanteric area.…”
Section: Plos Onesupporting
confidence: 81%
“…Some researchers used 3D grid-shaped of plastic with the dimensions of 170 mm × 170 mm × 250 mm to evaluate the image distortion of six MR scanners of Siemens and Philips companies. According to this phantom dimensions, the image distortion was less than 2 mm for all points (26) . In addition, Mah et al examined the effect of image distortion on the lateral and anterior-posterior (AP) separation of 12 patients via vendor distortion correction program.…”
Section: Introductionmentioning
confidence: 80%
“…There are different types of 3D printing technologies that can offer higher resolution and higher in-fill density print options than FDM 3D printing [167] (see Appendix B for a summary of 3D printing technologies used in medicine). Recently, selective laser sintering (SLS) has been used to generate a 3D printed phantom for MRI geometric distortion assessment [168]. For the purpose of this study, dual extrusion FDM 3D printing was found to be efficient and more cost effective than SLS, which was the alternate type of 3D printer at The Ottawa Hospital's Medical 3D Printing Laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The acrylic water-absorption issue can be prevented by draining the phantom housing after every use, or by filling the phantom housing with alternate MR compatible liquids such as mineral oil (with the drawback of this material being not as bright as H2O NiSO4 on T2w images). Additionally, with the use of a vibration plate, Jafar et al [168] described an effective method of minimizing air bubbles, which can further improve the accuracy of identifying the lattice intersection points for Cube C.…”
Section: Discussionmentioning
confidence: 99%